Botanical composition of a natural rangeland overseeded with annual ryegrass under N fertilization - Ávila, M.R. (2019)
The fertilization in rangelands has a positive effect in the forage production.  The increased nitrogen (N) availability improves plant growth and forage quality of native pastures. However, in the Pampa biome conditions of Rio Grande do Sul State, Brazil, these responses occur surprisingly fast and consistently. Therefore, the objective of this work was to quantify the N effect in the botanical composition of a natural pasture overseeded with annual ryegrass in Southern Brazil. The effects of three rates of N fertilization (zero, 100 and 200 kg N ha-1) were evaluated. Forage biomass was estimated on a monthly basis using the double sampling approach. The different botanical components of each forage sample were manually sorted in the laboratory. In order to calculate the Rényi diversity profile, two floristic composition evaluations were performed in the experimental area in December of 2010 and September of 2011. The ryegrass biomass production is highly affected by the N fertilization. The botanical composition of natural pastures modifies most probably by increasing ryegrass competition at early spring.